2020
DOI: 10.1111/dth.14017
|View full text |Cite
|
Sign up to set email alerts
|

Public interest in Raynaud's phenomenon: A Google Trends analysis

Abstract: Raynaud's phenomenon is a common disorder affecting body extremities and other vascular beds. As infodemiological methods have developed, online search tools could be used to explore the public interest of the disease. The study aimed to determine the annual trend, seasonal pattern, and associated topics of Raynaud's phenomenon. Google Trends was used to collect the data. "Raynaud syndrome" was selected as the search term. Data on monthly relative search volume (RSV) were collected from four selected countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Health informatics research is becoming increasingly integrated with public data from the internet as a result of the development of the intelligent internet, the advantages and competitiveness were shown in infodemiological studies for exploring human healthy behavior, including detecting the public interest and awareness of disease, understanding and monitoring the public's perception of disease management and treatment are also essential, Google Trends (GT) as an open tool which it can provide information on trends and the variations of online interest and usefulness was presented in analyzing human behavior toward health topics and in predicting disease occurrence and outbreaks, GT becoming the most popular tool for detecting online behavior [ 13 , 14 , 16 ]. In our study using Google search traffic data for further analysis, we revealed public interest and awareness that consist of annual trends, related topics, seasonal variation, geographic distribution, and the development influence of nasal polyps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health informatics research is becoming increasingly integrated with public data from the internet as a result of the development of the intelligent internet, the advantages and competitiveness were shown in infodemiological studies for exploring human healthy behavior, including detecting the public interest and awareness of disease, understanding and monitoring the public's perception of disease management and treatment are also essential, Google Trends (GT) as an open tool which it can provide information on trends and the variations of online interest and usefulness was presented in analyzing human behavior toward health topics and in predicting disease occurrence and outbreaks, GT becoming the most popular tool for detecting online behavior [ 13 , 14 , 16 ]. In our study using Google search traffic data for further analysis, we revealed public interest and awareness that consist of annual trends, related topics, seasonal variation, geographic distribution, and the development influence of nasal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the searching increasing trend was presented in the past decade, which is not only closely associated with the rapid development and wide application of the internet, but may reflect the increasing public interest even or incidence rate of nasal polyps to some extent, although the complete real-world epidemiological study that can reflect incidence rate globally was absent to date. GT analysis can obtain the seasonal variation and geographic distribution information and provide a positive understanding for identifying the influence of geographic distribution and seasonal variation on health information and diseases [ 16 18 ], further analyzing both seasonal variation and geographic distribution in search of annual trend was performed in our study, we separately selected the different the northern and southern hemisphere countries who have obviously and no-obvious seasonal variation for identifying the seasonal variations, that included the United States, Australia and Singapore, and results demonstrated and supported the seasonal variation of nasal polyps for the RSV (Fig. 3 ), especially, the peak for the RSV occurred in winter (December–January for the United States, and around July for Australia), the peak for the RSV of seasonal variation may reflect that directly associated with the pathophysiological characteristics and mechanism of NP, actually, for nasal polyps’ formation, which is a result of inflammatory outgrowths of paranasal sinus mucosa following chronic mucosal inflammation, although the pathogenesis is remained unclear, defects in the innate function of the airway epithelial barrier, including diminished expression of antimicrobial products and loss of barrier integrity, combined with colonization by fungi and bacteria likely all were probably contributed to chronic inflammation with elevated expression of many key inflammatory cytokines and chemokines, including IL-5, thymic stromal lymphopoietin (TSLP) and CCL11 in CRSwNP, these factors likely combine to drive the influx of a variety of immune cells, including eosinophils, mast cells, group 2 innate lymphoid cells and lymphocytes, which participate in the chronic inflammatory response within the nasal polyps [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to scientific interest, on the other hand, it is important to evaluate the interest in these topics among the population. The most widely used free tool for analyzing online behavior is Google Trends, which can also give real-time data about trends and changes in online interest over time for different terms and themes 28 30 . Electronic data is utilized in this field to monitor online interest in health problems and procedures, predict disease outbreaks, and assess the efficacy of health education efforts 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have used the Google Trends search data tool to assess patient interest in health topics and medical conditions and predicting behavior during a disease outbreak [12][13][14][15][16]. This tool produces normalized values reflecting interest in a given search term across a specified timeframe and location.…”
Section: Introductionmentioning
confidence: 99%